Sufism, Orthodoxy, and Nationalism in Modern Islamic Civilization in North Africa from The 19th- 20th Century - Dudung Abdurahman; Kholili Badriza (Universitas Islam Negeri Sunan Kalijaga, 2021)
The phenomenon of Sufism in the tariqa movements played a significant role in Islamic reform and the growth of nationalism in North Africa from the 19th to 20th centuries. This phenomenon which started as a neo-Sufism for Islamic reform, gradually turned into a nationalist movement. Therefore, Sufism is assumed to be a part of Islam that occupies the basic component of national identity and is a symbol of the struggle for independence of Muslim countries in North Africa. This study aims to discuss